Queen Victoria in Popular Fiction - Šramhauserová, Petra (Univerzita Pardubice, 2014)
This master thesis deals with the portrayal of the Queen Victoria captured in two works of popular fiction written as autobiographies and memoires. The analysis traces level of historical accuracy in works of popular fiction, further aspects of Victorian society along with the question of womanhood as a main motive of the story of not only the Queen but rather a woman, mother and a widow. Firstly, a problematic nature of popular fictions is discussed along with the phenomenon of mass culture and literary versus popular fiction. Secondly, key principles of autobiography and memoir are introduced. The practical part comprises of juxtaposition of fact and fiction demonstrated on I, Victoria by Cynthia-Harrod Eagles and Victoria Victorious by Jean Plaidy. Further, womanhood with its components such as motherhood, childbearing, widowhood, marriage, love and emotions are addressed. The way fictional story is mounted on history is summarized and evaluated in conclusion.
Královna Viktorie v Populární Fikci
Keywords: královna Viktorie; populární fikce; literární fikce; masová kultura; autobiografie; memoáry; historie; fikce; ženství; mateřství; vdovství; těhotenství; manželství; Queen Victoria; popular fiction; literary fiction; mass culture; autobiography; memoir; history; fiction; womanhood; motherhood; widowhood; childbearing; marriage